PERANCANGAN SISTEM INFORMASI PENGGAJIAN PEGAWAI PADA JOGJA BAY SLEMAN BERBASIS WEBSITE - Adzan Yogaswara (2021)
Payroll system is very important for financial activities in a company. In processing data at Jogja Bay, it is computerized but still simple, namely using Microsoft excel so that in processing data there will be potential for errors in calculating employee salaries, such as basic salary, overtime salary, salary deductions, transport fees and salary reports must be checked repeatedly. of every employee. The system development method used in this research is the waterfall method. The result of this research is a computerized payroll information system that can accommodate information from employees, employee salary data, employee salary reports. In the payroll system the author uses UML diagrams and MySQL in processing data and development tools used HTML and PHP. After researching this payroll system, the author hopes to make the work of each employee easier.